The effectiveness of safe city program in tourist city / Hasnor Syukriah Che Hassan , Siti Nadzirah Fitriadi and Nur Azilla Meli - Che Hassan, Hasnor Syukriah; Fitriadi, Siti Nadzirah; Meli, Nur Azilla (Faculty of Hotel and Tourism Management, 2015)
In recent years, safety aspect becomes one of the prominent issues in the urban tourist destinations.This is due to the frequent occurrence of crime such as murdering, snatching, kidnapping, robbery, sexual assault and vehicle stealing to tourists visiting city areas and it can become a threat to the tourism industry. Therefore, if tourist feels insecure or threatened in some destination, it may create negative impressions and experience towards the destination.These issues have led to the implementation of Safe City Program (SCP) in Malaysia which was introduced on 10 August 2004 by the Ministry of Housing and Local Government (MHLG) of Malaysia. Under this program, the safe city is classified as free from physical, social and mental threats, living environment that is secured and conducive at all times and the community is able to live in peace and harmony. Until recently, the concept of a safer city has been realized through the implementation of a crime prevention guideline outlined by the Department of Town and Country Planning (JPBD). This guideline consists of 23 measures of crime prevention approach through three important strategies which are environmental design initiatives, landscape design and education and public awareness. On December 2012, MLHG reported that SCP has been successfully implemented across its 149 local authorities across Malaysia. Moreover, it is also reported that at least 90% of major towns in Malaysia are categorized as good in managing crime. Ironically, previous research shown that, despite of Shah Alam was among the first to implement SCP, it was ranked the fifth highest crime rate among cities in Selangor. Therefore, it is important to notice this contradicted results expected from this program to other cities in Malaysia. This research was conducted among tourists visiting Kota Bharu, Kelantan. Kota Bharu is chosen as it is one of the popular tourism cities in the east coast of peninsular Malaysia with cultural heritage as the central attraction. In addition, Kota Bharu Municipal Council has launched its safe city program in 2010 and the aim of this study was to assess the effectiveness of SCP in this city. Convenience sampling was used among 384 tourists who are willing to participate this study. The results show that most of the respondents consider the effectiveness of SCP in Kota Bharu as "satisfied". In addition, police booth has been indicated as the most effective strategy of SCP implemented in Kota Bharu. This is inconsistent with previous researches in Putrajaya and Johor Bahru which surveillance camera (CCTV) has been assessed as the most effective strategy. In line with this current finding, it is recommended that various tourism bodies and municipalities need to ensure a continuous improvement on safe city program implementation through collaboration and joint responsibilities.